Комбинирование традиционных и инновационных технологий обучения при подготовке современных специалистов в высшей школе - Митина, О. А.; Юрченко, И. В. (My University, 2016)
Article reviewed the modern trends in education, combining them with traditional methods of learning in higher education. Merits and demerits of traditional and innovative methods of training are revealed. The main directions and objects of innovative transformations in pedagogics are defined.
Keywords: innovation; pedagogical technologies; traditional and innovative methods of training; combination of methods